Cutaneous squamous cell carcinoma in situ with extensive clear cell change - A report of two cases - Vladimír Bartoš; Milada Kullová (Our Dermatology Online, 2017)
Squamous cell carcinoma (SCC) of the skin includes many histologic subtypes with varying microscopic features and clinical behaviors. Clear cell SCC belongs to one of the rare histologic variants of this cutaneous malignancy. Herein, two cases are described in a 78-year- old man arising on the cheek and in a 79-year-old woman arising on the neck. In both examples, histology revealed an intraepidermal (in situ) SCC with a predominant clear cell change of malignant keratinocytes. In addition, a typical keratinizing squamous cell component was also present. Clear cell population showed apparent mitotic and proliferative activity. In one patient, it slightly stained with periodic acid-Shiff (PAS) method. Staining with alcian blue was negative in both cases. Knowledge on histomorphology and pathogenesis of this tumor entity is discussed.